Kuit: el compromiso de una empresa con la sostenibilidad a través del desarrollo tecnológico - Silva-Flores, Martha (2024)
This article is a case study that aims to show how Kuit, a social enterprise, addresses the challenge of technological management while meeting its social, environmental and economic business objectives. The study examines innovation through technological development as part of a business strategy to promote ethical and sustainable business practices, which are focused on the health and well-being of people through the production and distribution of kombucha. The relevance of the case study lies in showing the technological management strategy implemented by the founders of Kuit, which has led them to a process innovation and a patent application. This innovation has been recognized by the Secretariat of Innovation, Science and Technology of the State of Jalisco, with Kuit being one of the five finalists for the 2021 Jalisco Innovation Award. Innovation has allowed Kuit to be a sustainable company both technically and financially, fulfilling its social and environmental mission.